The Effect of Work-Life Balance and Work Environment on Employee Job Satisfaction - Deddy Iskandar; Irwin Ananta Vidada (Manunggal Halim Jaya, 2024)
Job satisfaction is an attitude and a sense of fulfillment that employees feel towards their jobs, which arises from the company's ability to meet all employee needs adequately. Employee job satisfaction is an essential component of human resource organizations and serves as a benchmark that companies need to improve to foster trust in the organization and ensure peak performance. This is also the case with PT. Bank Tabungan Negara Tbk Bintaro Jaya Branch, which has experienced suboptimal work-life balance and work environment conditions, causing employees to feel uncomfortable in their jobs. This study aims to analyze the influence of work-life balance and work environment in enhancing job satisfaction among employees at PT Bank Tabungan Negara Tbk Bintaro Jaya. A sample size of 53 respondents was taken using a non-probability sampling technique with a saturated sample method. This research employs a quantitative method with data analysis conducted using multiple linear regression analysis with the assistance of SPSS version 25.0. The results show that work-life balance has a positive and significant effect on job satisfaction, and the work environment also has a positive and significant effect on job satisfaction.